2017
DOI: 10.2147/ov.s145262
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virus delivery: from nano-pharmacodynamics to enhanced oncolytic effect

Abstract: With the advancement of a growing number of oncolytic viruses (OVs) to clinical development, drug delivery is becoming an important barrier to overcome for optimal therapeutic benefits. Host immunity, tumor microenvironment and abnormal vascularity contribute to inefficient vector delivery. A number of novel approaches for enhanced OV delivery are under evaluation, including use of nanoparticles, immunomodulatory agents and complex viral–particle ligands along with manipulations of the tumor microenvironment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 136 publications
0
21
0
Order By: Relevance
“…Despite pre-existing immunity having no measurable effect on the therapeutic outcome after intratumoral injection, innate and adaptive immune responses against circulating viruses may restrict their efficacy after intravenous administration [104,105]. PEGylation of OVs [106,107] or switching OV species during the course of treatment [108,109] can improve stealthiness and enhance treatment efficacy. Enveloped viruses can also be pseudotyped with different viral envelops [110][111][112], while changing the serotype of non-enveloped viruses could evade the immune response [113][114][115].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…Despite pre-existing immunity having no measurable effect on the therapeutic outcome after intratumoral injection, innate and adaptive immune responses against circulating viruses may restrict their efficacy after intravenous administration [104,105]. PEGylation of OVs [106,107] or switching OV species during the course of treatment [108,109] can improve stealthiness and enhance treatment efficacy. Enveloped viruses can also be pseudotyped with different viral envelops [110][111][112], while changing the serotype of non-enveloped viruses could evade the immune response [113][114][115].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…Vascular injection also has limitations. Tumor vasculature is markedly disorganized and more unstable than normal vessels [ 41 ]; this property makes vascular injections less reliable for downstream delivery of the virus to surrounding cancer cells. However, currently there are several avenues under investigation to stabilize these tissues and enhance delivery of cancer immunotherapy; some examples include the use of nitric oxide [ 42 ] and VEGF [ 43 ].…”
Section: Modes Of Ov Deliverymentioning
confidence: 99%
“…Entire pathogens, in particular recombinant oncolytic viruses, have been engineered to sustain selective replication into malignant cells [46,47]. However, experience with the use of these oncolytic viruses, originally thought as cytolytic agents, has shown that antitumor immune response against viral-infected cells is a fundamental factor for their anticancer efficacy [48]. Therefore, modern viral vectors are genetically engineered to also express cytokines and other immune stimulating factors [49].…”
Section: Intratumoral Delivery Of Pathogensmentioning
confidence: 99%